Learning from the licensing of a papaya variety developed by the public sector in Costa Rica: A case study - Salazar, Silvia; Jiménez, Luis; Falck-Zepeda, José B. (International Food Policy Research Institute, 2010)
The goal of the present case study is to describe the process that the University of Costa Rica's Office for Knowledge Management and Transfer (PROINNOVA) undertook to license the seeds of a new papaya variety, named Pococi, developed jointly by the University of Costa Rica (UCR) and the National Institute for Agricultural Technology (INTA, for its acronym in Spanish) from Costa Rica, in order to understand the institutional challenges that must be addressed by potential license seeking organizations in Costa Rica to ensure successful transactions. Learning from the multiple experiences dealing with the licensing context in this case study will certainly help ensure maximizing the benefits from licensing while minimizing costs and risks from such activity in Costa Rica.